Pediatric Orthopedic Surgical Emergencies - Abzug, Joshua M.; Abzug, Joshua M.; Herman, Martin J.; Herman, Martin J. (Springer New York : Imprint: Springer, 2012)
Care of pediatric orthopedic surgical emergencies is often provided by on-call orthopedic surgeons who primarily treat adults.  This book is designed to impart essential information that enables doctors to safely evaluate and treat the most common emergencies in pediatric orthopedic surgery. Each emergency scenario includes the keys to patient evaluation, operative considerations, and expected complications. Filled with technical pearls and tips based on clinical experience in this area, the editors and contributors to Pediatric Orthopedic Surgical Emergencies have created a single source for treatments and best practices in this area. Topics covered run the gamut from trauma (including the mangled extremity and compartment syndrome) to individual body regions (the spine, the upper and lower extremities) to infections and other conditions. Pediatric Orthopedic Surgical Emergencies is a convenient illustrated text for any physician seeking guidance for challenging, but not uncommon, pediatric emergencies.